The biological effects of strontium (88Sr) on Chinese cabbage - Weirong Zhang; Zheng Kang; Qiang Wang; Nianwei Qiu; Min Chen; Feng Zhou (Plant, Soil and Environment, 2020)
Steady-state strontium (88Sr) plays an important role in human health. Applying a proper amount of 88Sr to vegetables can improve their nutritional value. To investigate the biological effects of 88S on vegetables, three-leaf Chinese cabbage (Brassica rapa L.) seedlings were provided with a nutrient solution containing 0, 0.1, 0.2, 0.5, 1.0, 2.0, 5.0 and 10 mmol/L SrCl2 by the hydroponic culture. The results showed that SrCl2 at low concentrations (0.2 and 0.5 mmol/L) promoted the growth of Chinese cabbage, while SrCl2 at high concentrations (2.0-10.0 mmol/L)significantly inhibited the growth. SrCl2 at high concentrations did not decrease the chlorophyll content and protein content in Chinese cabbage leaves, nor did it affect the photosynthetic capacity of leaves. The main reason that SrCl2 at high concentrations inhibited the growth of Chinese cabbage was that strontium affected the absorption of calcium. SrCl2 at the concentration of 0.2 and 0.5 mmol/L could significantly increase leaf protein, chlorophyll, and water content and promote the growth of Chinese cabbage. The supplement of SrCl2 at these two concentrations may be beneficial to the growth and yield of Chinese cabbage.